Chromosomal abnormalities and copy number variations in children with idiopathic mental illness - O. S. Kurinnaia; I. Y. Iourov; S. G. Vorsanova (Обозрение психиатрии и медицинской психологии имени В.М. Бехтерева)
Genetic factors of mental illness are generally recognized. Here, it is shown that molecular karyotyping in combination with original bioinformatics methods offers the opportunity for effective uncovering genomic pathology, which may provide correct data on genetic factors for mental disorders in children.